Images and relics : theological perceptions and visual images in sixteenth-century Europe - Dillenberger, John (Oxford studies in historical theology., 1999)
John Dillenberger has written the first comprehensive account of the relation between the visual arts and theological currents in Europe during the first half of the sixteenth century. With an astute knowledge of the theology of the period and a keen interest in the lives and work of prominent artists, Dillenberger makes incisive connections that illuminate the cultural movements of the time.